RARE EARTH ELEMENTS IN QUARTZ-MUSCOVITE METASOMATITES OF THE PRIMORSKII FAULT, WESTERN BAIKAL AREA - Savel'eva V.B.; Zyryanov A.S.; Panteeva S.V. (My University, 2003)
The behavior of rare earth elements and yttrium was studied in the metamorphic rocks of the Sarma Group (PR1) and in the later quartz-muscovite metasomatites confined to the Primorskii fault zone in the western Baikal area. The metasomatites formed after the quartz-chloritoid and chloritoid-staurolite-garnet schists and garnet amphibolites during two metasomatic stages, including potassium metasomatism and acidic leaching. The rare earth elements were inert during the muscovitization of the chloritoid-staurolite-garnet schists, while the development of quartz-garnet-muscovite metasomatites after the chloritoid schists resulted in the rocks' enrichment in TRY, and the development of garnet-muscovite metasomatites after the garnet amphibolites was accompanied by the accumulation of TRCe and TRY in the rocks. The rare earth elements and yttrium were leached from the schists during silicification. Their bulk concentration in the silicified rocks is 3-6 times lower than that in the unaltered rocks, and the rock silicification resulted in a decrease in the TR Ce/TRY ratio from 4.3-11.8 to 2.2-2.6.